SDGS DISCLOSURE AND FINANCIAL PERFORMANCE: POINTS OF VIEW FROM GENDER DIVERSITY, CSR AND INDUSTRIAL SENSITIVITY - Izzaty, Khairina Nur; Setiyono, Taufiq Andre; Putri, Angie Marsha; Hamzah, Iffa Dania (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to examine the factors that are thought to encourage companies to disclose sustainable development goals (SDGs) in their sustainability reports and examine the impact of disclosing SDGs on the company's financial performance. Using a population of companies listed on the Indonesia Stock Exchange and carrying out sustainability reporting, the sample used in this study was 146 firm-years after being eliminated using a purposive sampling method. Quantitative research data was then processed using SPSS 26 software, using two multiple linear regression models. The statistical results show that for the first model, board of directors gender diversity has a significant negative effect on SDGs disclosure, CSR committee and industry sensitivity have a positive effect on SDGs disclosure, while board of directors and commissioners gender diversity and company size have no significant effect on SDGs disclosure. In the second model it is known that the disclosure of SDGs by the company is not able to significantly influence the company's financial performance.